THE INFLUENCE OF LEADERSHIP, MOTIVATION AND COMPETENCE ON THE PERFORMANCE OF EMPLOYEES OF PT. MODERNLAND REALTY TBK JAKARTA - Habibie, Irham (Dinasti Publisher, 2021)
This study aims to measure leadership, motivation and competence on the performance of employees of PT Modernland Realty TBK Jakarta. This research is quantitative in nature. The study population was all staff employees. The sampling technique was using nonrandom sampling, namely saturated samples with a total of 89 staff. This study uses multiple linear regression analysis. The results of the t-test state that leadership, motivation and competence partially have a significant positive effect on employee performance. The results of the F-test of leadership leadership, motivation and competence simultaneously have a significant positive effect on employee performance. Suggestions for further research include organizational factors, organizational justice, and job satisfaction as additional independent variables.